Strategi Penguatan Persepsi Nasabah: Pengaruh CRM Terhadap Kualitas Hubungan dan Customer Lifetime Value di PT. Bank Mandiri (Persero), Tbk Area Jakarta Tebet Supomo - Brando, Alan; Sadikin, Dikdik Saleh; Andriani, Meta; Budhijana, R. Bambang (STIE Indonesia Banking School, 2025)
Customer Relationship Management (CRM) is a conceptual paradigm on marketing management perspective that refer to practical series on the implementation of a strategic processes which aimed to improve the relationship quality with customers. Based on bank’s perspective, this paradigm has a significant role to establis long term profitability. The main purpose of this paradigm is to make customer’s loyalty which loyalty is the main problem of bank’s performance growth. The aim of this study is the implementation of CRM at Bank Mandiri in forming customer value which is reflected on historically of Bank Mandiri’s CES, CSAT, NPS, and SES Value. The method used in this study is random sampling method where customers were selected to answer the staements in questionnaire. The analyctical methods that used in this study is Structural Equation Modeling to test the direct effect and indirect effect for each variables. The result of this study show that the Customer Relationship Management has a positive and significant effect on Relationship Quality and Customer Lifetime Value, direct or indirect effect. The result of this study have implication for management, practitioners and academics that bank’s has to improve the capabilities of ther implementation of CRM to increase the relationship quality with customer to improve the customer lifetime value. Keywords: Customer Relationship Management, Relationship Quality, Customer Lifetime Value